Solar cells research and development of solar cells - Kolisnychenko, Stanislav (Trans Tech Publications, Ltd., 2015)
Solar energy possesses enormous potential as a source of affordable and inexhaustible energy. Solar energy is utilized with the help of various technologies and, in particular, photovoltaic technology, based on photovoltaic elements which provide direct conversion of solar energy into electricity. The compilation "Research and Development of Solar Cells" covers papers concerning various aspects of the design, research and manufacture of photovoltaic cells, as they have been selected from the library of Trans Tech Publications Inc. from 2010 to 2014 inclusive